Magnetotransport Measurements in Overdoped Mn:Bi2Te3 Thin Films - Angadjit Singh; Varun S. Kamboj; Crispin H. W. Barnes; Thorsten Hesjedal (Crystals)
Introducing magnetic dopants into topological insulators (TIs) provides a pathway to realizing novel quantum phenomena, including the quantum anomalous Hall effect (QAHE) and axionic states. One of the most commonly used <semantics>3d</semantics> transition metal dopants is Mn, despite its known tendency to be highly mobile and to cause phase segregation. In this study, we present a detailed magnetotransport investigation of Mn-overdoped Bi2Te3 thin films using field-effect transistor architectures. Building on our previous structural investigations of these samples, we examine how high Mn content influences their electronic transport properties. From our earlier studies, we know that high Mn doping concentrations lead to the formation of secondary phases, which significantly alter weak antilocalization behavior and suppress topological surface transport. To probe the gate response of these doped films over extended areas, we fabricate field-effect transistor structures, and we observe uniform electrostatic control of conduction across the magnetic phase. Inspired by recent developments in intrinsic topological systems such as the MnTe-Bi2Te3 septuple-layer compounds, we explore the influence of embedded ferromagnetic chalcogenide inclusions as an alternative route to engineer magnetic topological states and potentially expand the operational temperature range of QAHE-enabled devices.